Open Governance, Based on the Principles of Accountability and Transparency, as the Foundation of a Democratic Society on the Example of the Public Sector of Georgia - Mumladze, Giorgi (European Scientific Journal, ESJ, 2023)
Transparency and openness are one of the mechanisms for implementing good governance. Both of them help create conditions for citizens to evaluate the decisions that the government makes on their behalf. Transparency and citizen participation also ensure that citizens' needs are met and that their positions are taken into account in the decision-making process. Effective transparency and engagement help to eradicate corruption and government malfeasance. At the same time, through transparency and engagement, citizens' trust can be increased. Transparency and engagement also ensure better decision-making by the government and more efficient delivery of public services (Radin, 2006). The relevance of the issue is emphasized by the fact that accountability and transparency represent an important valuable principle that increases the degree of legitimacy of the civil sector and, naturally, affects the effectiveness of the development of public organizations (Walker, 2002). Due to the fact that the accountability of public organizations with donors is regulated by the contracts signed between them, and the accountability with the state is regulated by legislation, special attention was paid to the accountability and transparency of the sector in relation to the public. It is recognized that in order to achieve a high degree of legitimacy of the sector, it is important to raise awareness of public organizations, increase public trust in them and create a positive image (Schedler, 2002,7-16).